In Terms of Music Teachers, the Evaluation of Music Types in the Curriculum for Music in Secondary Education in Turkey - Gül, Gülnihal (European Journal of Social Science Education and Research, 2014)
Along with the establishment of the Republic, a song repertoire consisting of transferred songs was previously endeavoured to be formed by taking school music samples of foreign countries and writing Turkish words below them. Afterwards, with the same percept, an imitation songs repertoire was attempted to be formed by our composers. Since the 1950s, the idea that school music should be on the axis of folk music and that music education should be carried out through school music samples composed from the close environment of the child has begun to take place. Together with the various developments since the 1970s, the tendency towards soft music has strengthened in society and also interest in Turkish classical music has increased. Moreover, since the 1970s, soft and classical music samples have begun to be used in music education, which was built on folk music in 1968. Thus, high school music teaching programs which went into effect in 1986 were prepared accordingly. Today, the sense that bringing to the classroom appropriate samples of vital music types in society, getting the student to learn at least one example of each music type and introducing these types is dominating. In this study, music types in middle school music teaching programs in Turkey were endeavoured to be evaluated in terms of music teachers. The subject was researched with the case study method which is one of the qualitative research methods. The oriented exemplification method was used in the study and 5 music teachers working in a middle school participated in the study group. The data was analysed by forming the necessary coding and themes. According to the obtained findings, results and suggestions were given place.